Beating the global odds : successful decision-making in a confused and troubled world / Paul A Laudicina. - Laudicina, Paul A.
The Answer to Global Overload Contending with the 24/7 news cycle and an endless barrage of choices and information has stymied leadership and decision-making strategies among those at the top. But we all know, this is not a just a problem for the elite. The broad-based reaction to this chaotic, unmanageable assault has been to retrench, and to focus on immediate, controllable decisions. In the process.